ANALISA PENGENDALIAN BIAYA DAN WAKTU PADA PROYEK KONSTRUKSI DENGAN METODE EARNED VALUE MANAGEMENT (EVM) - Juliana Juliana (LPPM, 2016)
Implementation of the project must have a clear direction and goals so that the planned results can be achieved more optimal. Monitoring, evaluation, and control needs to be done particularly with respect to cost and time of implementation of the project so that it can be seen the performance of the project as well as to predict the cost and time to expiration of the project if the project is experiencing delays in their completion, by using Earned Value Management (EVM) is a method used in project management, which facilitates the control of time and cost. But in practice the management of construction projects undertaken contractor in Indonesia have yet to implement fully EVM. Especially the use of information systems in the management of construction projects yet optimally included in applying methods of EVM in project control.A construction project implementation will certainly be helped by the information system. Delays can work immediately known so that the control process so much easier. Not only in the control process but also in the process of document storage and data projects, because of the use of information systems document storage process and the data of the project becomes more easy and quick Keywords: construction project, cost and time, earned value